Prognosis following surgical bypass compared with laparotomy alone in unresectable pancreatic adenocarcinoma. Issue 9 (2nd June 2016) - Insulander, J; Sanjeevi, S; Haghighi, M; Ivanics, T; Analatos, A; Lundell, L; Del Chiaro, M; Andrén-Sandberg, Å; Ansorge, C
Abstract: Background: Resection with curative intent has been shown to prolong survival of patients with locoregional pancreatic ductal adenocarcinoma (PDAC). However, up to 33 per cent of patients are deemed unresectable at exploratory laparotomy owing to unanticipated locally advanced or metastatic disease. In these patients, prophylactic double bypass (PDB) procedures have been considered the standard of care. The aim of this study was to compare PDB with exploratory laparotomy alone in terms of impact on postoperative course, chemotherapy and overall survival. Methods: This retrospective observational cohort study (2004–2013) was conducted using a prospective institutional database. Patients with histologically confirmed, unresectable PDAC were included. Relationships between PDB procedures, exploratory laparotomy alone, postoperative chemotherapy and best supportive care were investigated by means of Cox regression. Overall survival was compared using Kaplan–Meier estimations and log rank test. Results: Of 503 patients with PDAC scheduled for resection with curative intent, 104 were deemed unresectable at laparotomy (resection rate 79·3 per cent). Seventy-four patients underwent PDB procedures and 30 had exploratory laparotomy alone. PDB and exploratory laparotomy were similar in terms of perioperative mortality, initiation of chemotherapy and overall survival. Compared with best supportive care, postoperative chemotherapy prolonged survival (8·0 versus 14·4 months in locally advanced PDAC, P = 0·007; 2·3 versus 8·0 months in metastatic PDAC, P < 0·001). Patients undergoing chemotherapy following exploratory laparotomy alone had longer median overall survival than patients undergoing chemotherapy following PDB procedures (16·3 versus 10·3 months; P = 0·040). Conclusion: Patients with pancreatic cancer deemed unresectable at laparotomy may derive survival benefit from subsequent chemotherapy as opposed to supportive care alone. At laparotomy, proceeding with a bypass procedure for prophylactic symptom control may be prognostically unfavourable. Abstract : Double bypass may be worse